Economically sustainable shade design for feedlot cattle - Maia, Alex S. C.; Moura, Gustavo A. B.; Fonsêca, Vinicius F. C.; Gebremedhin, Kifle G.; Milan, Hugo M.; Chiquitelli Neto, Marcos; Simão, Bruno R.; Campanelli, Victor Paschoal Consentino; Pacheco, Rodrigo Dias Lauritano (Frontiers in Veterinary Science, 2023)
Provision of shade reduces radiant heat load on feedlot cattle, thus reducing demand of water and energy for thermoregulation. While the positive effects of shade on animal welfare are widely known, the literature lacks data on the magnitude of its economic impacts. In this study, we propose the concept of novel shade design to prove that a correctly oriented and dimensioned roof structure, which optimizes shade to be displaced within the pens, motivates cattle to seek shade, protect them from short-wave solar radiation, and is resilient to counteract weather adverse conditions. The beneficial outcome is improvement in animal welfare and productive performance, as well as increments on financial return and sustainability. To attest these benefits, eight hundred B. indicus × Bos taurus bulls were randomly assigned in pens with or without shade from a galvanized steel-roof structure. Performance data (e.g., dry matter intake, body weight gain, feed efficiency and hot carcass weight) and heat stress indicators (e.g., subcutaneous temperature, body-surface temperature, respiratory rate and water intake) were assessed along the study period. The economic outcomes derived from shade implementation were determined using the net present value. Meteorological variables were also monitored every 1 min, and grouped in a thermal comfort index for feedlot cattle, the InComfort Index (InCI). The shade structure efficiently reduced radiant heat load on cattle in pens with shade. According to the classification of the InCI, during very hot days (InCI > 0.6; around noon with mean solar radiation above 800 W m−2 and mean air temperature above 33°C), greater proportion (80%) of animals in shaded pens were using shade. Under such circumstances, cattle in shade had water intake reduced by 3.4 L per animal, body temperature was lower by 5°C, subcutaneous temperature was lower by 1°C and respiration rate was lower by 10 breaths min−1 compared to animals in pens without shade (P = 0.0001). Although dry matter intake was similar (P = 0.6805), cattle in pens with shade had higher average daily gain reflected in a heavier hot carcass weight (8 kg animal−1; P = 0.0002). Considering an initial investment of 90 per animal to build a structure that lasts 15 years, the expected payback time is four finishing cycles ( 110 days per cycle). In conclusion, this study confirms that the proposed novel shade design is economically profitable, improves performance, and enhances animal welfare.